Produksi Kitab Tafsir Lokal dalam Menunjang Dakwah Moderasi Beragama Ulama Pondok Pesantren As'adiyah Sengkang - HS, Muhammad Alwi; Fatikhatul Faizah; Kasim, Muhammad Naufal Dliyanto (Al-Wasatiyah: Journal of Religious Moderation, 2024)
This study examines the tradition of Qur'an interpretation by ulama of As'adiyah pesantren, focusing on Tafsir Al-Qur'an Al-Karim bi Al-Lughah Al-Buqisiyyah Juz Alif Lam Mim (1958) and Juz Amma (1974) by AGH. Muhammad Yunus Maratan, Tarjumah Al-Quran Al-Karim: Tarjumanna Akorang Malebbi 'e Mabbicara Ogi (1979) by AGH. Hamzah Manguluang, Tafsir Al-Munir (1980) by AGH. Daud Ismail, and Tafsere Akorang Mabbasa Ogi (1988) by AGH. Abdul Muin Yusuf. These sources are described and analyzed to find the function of tafsir for Lontara-Bugis-speaking pesantren ulama in South Sulawesi. From this, this article concludes that although different in presentation, the commentators made their books as a typical da'wah movement of As'adiyah pesantren, both to the pesantren community (santri) and the people of South Sulawesi. This movement supports As'adiyah's orientation as a pesantren that produces many preachers in South Sulawesi. Likewise, the authors of the tafsir have a high social role as ulama in Bugis society. In addition, the use of Lontara-Bugis is not only a language of communication between interpreters and readers, but also a safeguard for the dissemination of the identity and existence of the Bugis culture.